Prevalencia de Dipylidium caninum en caninos domésticos (Canis lupus familiaris) en la parroquia de Uyumbicho cantón Mejía - Chen Villamarín, Yan Mishell (Ecuador : Latacunga: Universidad Técnica de Cotopaxi (UTC), 2021)
Parasitic diseases are a public health problem. When an animal is infected with parasites, it is a carrier, giving rise to the direct or indirect transmission of various pathologies that affect other animals or, in turn, humans since there is a close bond of coexistence. The present investigation was carried out in the Province of Pichincha, a rural parish of Cantón Mejía. The objective was to identify Dipylidium caninum present in canine fecal samples from the Uyumbicho sector related to the variables of sex and age. Fecal matter samples were collected from 100 domestic canines with their respective data and owners. The study population was distributed in various age ranges, first from 0-1 year, second from 1-3 years, and finally over three years. 3 g of fresh feces were taken, which were processed in the Parasitology Laboratory of the Technical University of Cotopaxi using the Sheather flotation technique. Of the results obtained, 12% of 100 canines were positive for Dipylidium caninum, of which eight positive cases (12.3%) correspond to males and four positive cases (11.4%) to females. Concerning the age group, it was determined that from 0-1 year, 6 (30%) cases are positive; 1-3 years, 3 (6.6%) cases are positive, and over three years, 3 (8.5%) of cases are positive. Las enfermedades parasitarias constituyen un problema de salud pública. Cuando un animal está infectado con parásitos, es un portador, dando lugar a la trasmisión directa o indirecta de varias patologías que afectan a los demás animales o a su vez al ser humano ya que existe un estrecho lazo de convivencia. La presente investigación se realizó en la Provincia de Pichincha, parroquia rural del Cantón Mejía, el objetivo fue identificar Dipylidium caninum presentes en muestras fecales caninas del sector de Uyumbicho relacionado con las variables de sexo y edad. Se recolectaron muestras de materia fecal de 100 caninos domésticos con sus respectivos datos y propietarios. La población de estudio se distribuyó en varios rangos de edades: primero de ...